The use of ChatGPT in the Indonesian ELT context: A systematic review - Syairofi, Ahmad; Emilia, Emi; Purnawarman, Pupung (Journal of Research on English and Language Learning (J-REaLL), 2025)
This study investigates the integration of ChatGPT as an educational technology tool within the Indonesian English Language Teaching (ELT) context. Utilizing a systematic review methodology, twelve peer-reviewed articles indexed in the Scopus database were selected for analysis to examine emerging trends, pedagogical applications, perceived benefits, and associated challenges of ChatGPT in EFL education. Through content analysis, the findings reveal that 2024 witnessed the highest publication output, with higher education identified as the most commonly explored educational setting. Qualitative research designs predominated among the reviewed studies. ChatGPT was employed for a variety of pedagogical purposes, including content and idea generation, feedback provision, linguistic revision, paraphrasing, grammar checking, teaching material development, lexical and collocational enhancement, personalized learning, and improving textual coherence and cohesion. Reported benefits encompass grammar correction, resource accessibility, idea generation, vocabulary expansion, and formative feedback. Conversely, challenges include user over-reliance, ethical concerns, informational inaccuracies, insufficient cultural contextualization, embedded biases, and limitations related to prompt formulation. The findings imply a critical need for future research that expands into secondary education contexts, utilizes quantitative or mixed-method approaches, addresses the identified limitations of ChatGPT in educational settings, and employs longitudinal designs to assess its sustained impact on language learning.